Hematological Parameters of Reintroduced Eurasian Beavers (Castor fiber Linnaeus, 1758): A Post-Reintroduction Study - Enkhmaa, Enkhbat; Ulam-Urnukh, Bayanmunkh; Adiya, Yansanjav (Proceedings of the Institute of Biology, 2024)
Hematological analysis is essential in evaluating both the challenges and successes of animal reintroduction programs worldwide. It serves as a key tool for assessing the health of individuals being prepared for release and for deepening our physiological knowledge of mammalian species. This study provides a comprehensive assessment of age- and sex-specific hematological profiles in Eurasian beavers reared under controlled conditions as part of the Gachuurt Beaver Reintroduction and Breeding Project. 18 hematological parameters were analyzed from blood samples of 26 individuals. While no statistically significant differences were observed between sexes, age-related differences were noted. Significant variations were found in body weight (p<0.0001), tail width (p<0.0002), hemoglobin concentration (p<0.0494), granulocyte count (p<0.0494), lymphocyte percentage (p<0.0157), granulocyte percentage (p<0.01), mean corpuscular hemoglobin (p<0.0181), and platelet count (p<0.0029). These results contribute essential baseline data for the health monitoring and conditioning of Eurasian beavers, supporting improved reintroduction strategies and long-term conservation planning. Our findings indicate that the concentrations of blood parameters in mature beavers are higher than those in younger and older individuals, reflecting a higher metabolic rate and normal cellular regeneration in fully mature animals. Сэргээн нутагшуулж буй голын минжний (Castor fiber Linnaeus, 1758) гематологийн судалгааны дүнгээс Хураангуй. Дэлхий нийтээр амьтан сэргээн нутагшуулах явцад гарсан амжилт, алдаа дутагдлаа үнэлэх, сэргээн нутагшуулсан бодгалийн эрүүл мэндийн нөхцөл байдлыг тодорхойлох, хөхтөн амьтны физиологийн шинэ мэдлэг хуримтлуулахад цусны шинжилгээг өргөн ашиглаж байна. Гачууртын минж нутагшуулах, үржүүлэх төслийн нэгж хариуцан тэжээвэр нөхцөлд өсгөн үржүүлж буй голын минжний цусны үндсэн үзүүлэлтүүд, тэдгээрийн хоорондын хамаарлыг нас, хүйсээр ялган тодорхойлсон үр дүнг энэхүү өгүүлэлд тусгав. Судалгааны үр дүнд нийт 18 гематологи үзүүлэлтийн дундаж утгыг 26 бодгалийн дээжинд тодорхойлсон бөгөөд хүйсийн хооронд статистик ач холбогдолтой ялгаа ажиглагдаагүй. Наснаас хамаарч биеийн жин (p<0.0001), сүүлний өргөн (p<0.0002), гемоглобин (p<0.0494), гранулоцит эсийн тоо (p<0.0494), нийт эсэд эзлэх лимфоцит эсийн хувь (p<0.0157), гранулоцит эсийн нийт эсэд эзлэх хувь (p<0.01), нэг улаан эсэд ноогдох гемоглобины дундаж жин (p<0.0181), тромбоцит эсийн тоо (p<0.0029), тус тус статистик ялгаатай тодорхойлогдов. Судалгаанаас харахад бие гүйцсэн бодгалиудын цусны үндсэн хувьсагчуудын агууламж залуу болон хөгшин бодгалиудын цусны бүрдэл хэсгээс их байна. Энэ нь бие гүйцсэн амьтдад бодисын солилцоо өндөр, эсийн нөхөн төлжилт хэвийн явагдаж байгааг харуулж байна. Түлхүүр үгс: Голын минж, цусны үндсэн үзүүлэлт, хувьсагчууд, сэргээн нутагшуулалт